The effect of temperature and other factors on plastics and elastomers - Mckeen, Laurence W. (PDL handbook series., 2014)
This reference guide brings together a wide range of critical data on the effect of temperature on plastics and elastomers, enabling engineers to make optimal material choices and design decisions. The effects of humidity level and strain rate on mechanical and electrical properties are also covered. The data are supported by explanations of how to make use of the data in real world engineering contexts. High (and low) temperatures can have a significant impact on plastics processing and applications, particularly in industries such as automotive, aerospace, oil and gas, packaging, and medical devices, where metals are increasingly being replaced by plastics. Additional plastics have also been included for polyesters, polyamides and others where available, including polyolefins, elastomers and fluoropolymers. Entirely new sections on biodegradable polymers and thermosets have been added to the book. The level of data included - along with the large number of graphs and tables for easy comparison - saves readers the need to contact suppliers, and the selection guide has been fully updated, giving assistance on the questions which engineers should be asking when specifying materials for any given application. Trustworthy, current thermal data and best practice guidance for engineers and materials scientists in the plastics industry. More than 1,000 graphs and tables allow for easy comparison between plastics. Entirely new sections added on biopolymers and thermosets.